β-grain size effect on the 18R-martensite microestructure in Cu-based SMA - la Roca, Paulo Matías (2015)
A systematic experimental analysis based on the assessment of the mean martensite plate size in sub-grain domains was implemented to characterize the martensitic microstructure morphology in polycrystalline Cu-based shape memory alloys. Experimental data was collected by light and electron microscopy, analyzing polycrystalline materials of grain size (d) in a wide range: from ﬁne-grained material with grain size of about 500 nm (ribbons and strips obtained by rapid solidiﬁcation techniques ) to single-crystals of 6 mm diameter (grown by the Bridgman method). In the d range below 100 µm, a lineal relationship between the average width of the martensite plates (h plate ) and the mean grain size was obtained for thermal-induced martensite transformation (T MT ). Above this value (d > 100 µm), such relation is no longer valid, and h plate Becomes independent of grain size.